Indole-Substituted Benzothiazoles and Benzoxazoles as Selective and Reversible MAO-B Inhibitors for Treatment of Parkinson's Disease - Nam, Min-Ho; Park, Moosung; Park, Hyeri; Kim, Youngjae; Yoon, Seulki; Sawant, Vikram Shahaji; Choi, Ji Won; Park, Jong-Hyun; Park, Ki Duk; Min, Sun-Joon; Lee, C. Justin; Chooaii, Hyunah (AMER CHEMICAL SOC, 2017)
To develop novel, selective, and reversible MAO-B inhibitors for safer treatment of Parkinson's disease, benzothiazole and benzoxazole derivatives with indole moiety were designed and synthesized. Most of the synthesized compounds showed inhibitory activities against MAO-B and selectivity over MAO-A. The most active compound was compound 5b, 6-fluoro-2-(1-methyl-IN-indol-5-yl)benzo[d]-thiazole with an IC50 value of 28 nM with no apparent effect on MAO-A activity at 10 mu M. Based on the reversibility assay, compound 5b turned out to be fully reversible with over 95% of recovery of enzyme activity after washout of the compound. Compound Sb showed a reasonable stability in human liver microsomes and did not affect the activities of CYP isozymes, suggesting an absence of high-risk drug-drug interaction. In an in vivo MPTP-induced animal model of Parkinson's disease, oral administration of compound 5b showed neuroprotection of nigrostriatal dopaminergic neurons as revealed by tyrosine hydroxylase staining and prevention of MPTP-induced parkinsonism as revealed by motor behavioral assay of vertical grid test. In summary, the novel, reversible, and selective MAO-B inhibitor compound 5b was synthesized and characterized. We propose compound 5b as an effective therapeutic compound for relieving parkinsonism.
Keywords: MONOAMINE-OXIDASE-B; L-DOPA; IN-VITRO; DRUG; SAFINAMIDE; THERAPY; METAANALYSIS; DERIVATIVES; RASAGILINE; METABOLISM